Peranan Pendidikan Kristen Dalam Membentuk Karakter Generasi Muda Di Era Digital - Damanik, Roy; Yuli, Purwisasi (REAL DIDACHE: Journal of Christian Education, 2024)
This study aims to analyze the role of Christian education in shaping the character of youth in the digital era. The background of this research stems from the observation that young people tend to dislike being regulated, prefer to follow their own desires, distance themselves from community, and spend significant time interacting in the virtual world, which they consider a trendy culture. The primary focus of this study is to understand how Christian education can adapt to contemporary challenges and fulfill the church's calling to be the light and salt of the world. This research will address questions regarding the understanding of Christian education in the digital age and its role in this context. Additionally, this study discusses the challenges of Christian religious education in the digital era, highlighting five roles of the church in shaping the character of youth: character formation, instilling discipline, fostering a sense of responsibility, instilling values of honesty, and nurturing a fear of God. The implementation of these strategies varies, and there is room for enhancing understanding and application, which is essential for shaping the character of the church's future generation. Keywords: christianity; digital era; education; role; young generationAbstrakPenelitian ini bertujuan untuk menganalisis peran pendidikan Kristen dalam membentuk karakter generasi muda di era digital. Latar belakang penelitian ini berakar pada fakta bahwa generasi muda cenderung tidak suka diatur, lebih memilih mengikuti keinginan sendiri, menjauh dari komunitas, dan menghabiskan waktu berinteraksi di dunia maya, yang dianggap sebagai budaya yang sedang tren. Fokus utama penelitian ini adalah untuk memahami bagaimana pendidikan Kristen dapat beradaptasi dengan tantangan zaman dan memenuhi panggilan gereja sebagai terang dan garam dunia. Penelitian ini akan menjawab pertanyaan mengenai pemahaman pendidikan Kristen di era digital serta perannya dalam konteks tersebut. Selain itu, penelitian ini membahas tantangan pendidikan agama Kristen di era digital, dengan menyoroti lima peran gereja dalam membentuk karakter generasi muda: pembentukan karakter, penanaman kedisiplinan, rasa tanggung jawab, nilai kejujuran, dan sikap takut akan Tuhan. Implementasi strategi ini bervariasi, dan terdapat ruang untuk meningkatkan pemahaman serta aplikasinya, yang sangat penting untuk membentuk karakter generasi muda gereja di masa depan.Kata Kunci: era digital; generasi muda; kristen; pendidikan; peranan